Microstructural, optical, and magnetic properties and specific absorption rate of bismuth ferriteSiO2 nanoparticles - Juwita, Erna; Sulistiani, Fitria Ayu; Darmawan, Mahardika Yoga; Istiqomah, Nurul Imani; Suharyadi, Edi (Materials Research Express, 2022)
In this study, the microstructural, optical, and magnetic properties and specific absorption rate (SAR) of bismuth ferrite/SiO2 nanoparticles were successfully investigated. The coprecipitation method was used to synthesize the nanoparticles. X-ray diffraction patterns showed the presence of sillenite-type Bi25FeO40 with a body-centered cubic structure. The crystallite size of Bi25FeO40 was 35.0 nm, which increased to 41.5nmafter SiO2 encapsulation. Transmission electron microscopy images confirmed that all samples were polycrystalline. The presence of Si–O–Si (siloxane) stretching at 1089 cm−1 in Fourier transforminfrared spectra confirmed the encapsulation of SiO2.Magneticmeasurements at roomtemperature indicated weak ferromagnetic properties of the samples. The coercivity of the bismuth ferrite nanoparticleswas 78Oe,which increased after SiO2 encapsulation. In contrast, their maximummagnetization, 0.54 emu g−1, reduced after SiO2 encapsulation.The determined bandgap energy of the bismuth ferrite nanoparticles was approximately 2.1 eV,which increased to 2.7 eVafter SiO2 encapsulation. The effect of SiO2 encapsulation on the SARof the sampleswas investigated using a calorimetricmethod. The SARvalues of the bismuth ferrite nanoparticleswere 49, 61, and 84mWg−1 under alternatingmagnetic field (AMF) strengths of 150, 200, and 250Oe, respectively,which decreased after SiO2 encapsulation.Themaximummagnetization and theAMF strength influenced the SARof the nanoparticles. The results showed that SiO2 has a significant effect in determining the microstructural, optical, andmagnetic properties and SARof the nanoparticles.